Abnormal Esophageal Scintigraphy Associates With a Distinct Clinical Phenotype in Patients With Systemic Sclerosis - Antonio Salas; Lisa R. Yanek; Laura K. Hummers; Ami A. Shah; Zsuzsanna H. McMahan (2025)
Objective In systemic sclerosis (SSc), absent contractility (AC) rather than ineffective esophageal motility on manometry is associated with a severe esophageal and extraintestinal phenotype. We sought to determine whether slow esophageal transit on scintigraphy associates with a comparable clinical phenotype to that of AC on manometry, as scintigraphy may serve as a noninvasive approach to risk‐stratify patients with SSc. Methods Clinical, demographic, and serologic features were compared between patients with and without delayed esophageal transit on scintigraphy. University of California Los Angeles Scleroderma Clinical Trials Consortium Gastrointestinal Tract (GIT) 2.0 scores measured GI symptoms, Medsger scores measured physician‐assessed SSc disease severity, and the Composite Autonomic Symptom Score 31 survey evaluated dysautonomia symptoms. Results Of 131 patients, 79 (60%) had delayed esophageal transit by scintigraphy. Patients with delayed esophageal transit were more likely to have diffuse SSc (24 [32%] vs 11 [22%]; P = 0.024), severe lung involvement (22 [41%] vs 7 [19%]; P = 0.034), severe Raynaud (36 [47%] vs 15 [31%]; P = 0.063), and a higher median (interquartile range [IQR]) diarrhea GIT score (0.5 [IQR 0–1] vs 0 [IQR 0–1]; P = 0.050). Lower diffusing capacity of the lungs for carbon monoxide values correlated with a higher esophageal transit time (ρ = −0.32; P = 0.014). After adjusting for disease duration, delayed esophageal transit was significantly associated with severe Medsger lung scores, severe Raynaud phenomenon, and higher modified Rodnan skin scores. Conclusion Patients with delayed esophageal transit by scintigraphy have a more severe SSc phenotype, similar to patients with AC, on esophageal manometry. Further studies should validate esophageal scintigraphy as a tool to identify patients with SSc with AC who may develop specific GI and extraintestinal complications.